Disinfection of water with new chitosan-modified hybrid clay composite adsorbent. Issue 8 (August 2017) - Unuabonah, Emmanuel I.; Adewuyi, Adewale; Kolawole, Matthew O.; Omorogie, Martins O.; Olatunde, Olalekan C.; Fayemi, Scott O.; Günter, Christina; Okoli, Chukwunonso P.; Agunbiade, Foluso O.; Taubert, Andreas
Abstract: Hybrid clay composites were prepared from Kaolinite clay and Carica papaya seeds via modification with chitosan, Alum, NaOH, and ZnCl2 in different ratios, using solvothermal and surface modification techniques. Several composite adsorbents were prepared, and the most efficient of them for the removal of gram negative enteric bacteria was the hybrid clay composite that was surface-modified with chitosan, Ch-nHYCA1:5 (Chitosan: nHYCA = 1:5). This composite adsorbent had a maximum adsorption removal value of 4.07 × 10 6 cfu/mL for V. cholerae after 120 min, 1.95 × 10 6 cfu/mL for E. coli after ∼180 min and 3.25 × 10 6 cfu/mL for S. typhi after 270 min. The Brouers-Sotolongo model was found to better predict the maximum adsorption capacity ( qmax ) of Ch-nHYCA1:5 composite adsorbent for the removal of E. coli with a qmax of 103.07 mg/g (7.93 × 10 7 cfu/mL) and V. cholerae with a qmax of 154.18 mg/g (1.19 × 10 8 cfu/mL) while the Sips model best described S. typhi adsorption by Ch-nHYCA1:5 composite with an estimated qmax of 83.65 mg/g (6.43 × 10 7 cfu/mL). These efficiencies do far exceed the alert/action levels of ca. 500 cfu/mL in drinking water for these bacteria. The simplicity of the composite preparation process and the availability of raw materials used for its preparation underscore the potential of this low-cost chitosan-modified composite adsorbent (Ch-nHYCA1:5 ) for water treatment.